METHODOLOGICAL APPROACHES TO ANALYSIS OF INNOVATION PROCESSES IN ENTREPRENEURSHIP (Economic journal of Lesya Ukrainka Volyn National University, 2020)
Introduction. The effectiveness of the innovation process at both global and national or regional levels depends on the successful theoretical grounding and in-depth scientific developments in the field. The theoretical basis of such developments is the search and further use of appropriate methodology for the study of phenomena that trigger innovative development of entrepreneurship and to best describe the cause and effect of trends occurring in the implementation of risky activities. The need to involve a common scientific methodology in the study of innovation processes in entrepreneurship is due to the fact that any innovative idea, innovation or scientific discovery is preceded by a thorough critical evaluation of the content of the main categories, concepts, definitions of the outlined phenomenon. In the process, further revision or authoring of approaches to interpreting existing and developing new theoretical concepts is possible. The purpose of the article. The purpose of the article is to determine the feasibility of applying some general scientific approaches in the study of the implementation of innovative processes in entrepreneurship. Results. Our problematic loci and the conceptual approaches to their solution emerge as interconnected components that are implemented in a comprehensive way. Being deeply synthesized in the methodology of researching innovative entrepreneurship, they have considerable cognitive and constructive potential from the standpoint of science. Conclusions. The above approaches to the methodology of research of innovative processes in entrepreneurship prove the need for their constant review and improvement in the modern times. The analysis of these approaches testifies to the necessity of their complex application, which will allow to scientifically grounded and carefully conduct research of real innovation processes, peculiarities of activity of institutes, as well as to logically and substantively present the main perspective goals, mechanisms, characteristics and regularities of functioning of national innovative entrepreneurship, its concrete historical and evolutionary form.
Keywords: innovative entrepreneurship, methodology, synergistic approach, bifurcations, adaptability, life cycle.